Differences in Hardiness Between 8th Grade Students of Superior and Regular Class in SMPN 1 Ngunut Tulungagung - Yogi Pratama, Ahmad; Farida Tantiani, Farah (KnE Social Sciences, 2022)
During this Covid-19 pandemic, almost all parts of the world are affected, including education process in school. At this time, students are learning from home, which causes many new challenges both in terms of physical and psychological. This psychological challenge can cause great pressure on students, including students from superior schools such as SMPN 1 Ngunut. One of the factors that can help students manage their psychological pressure better is their personality such as hardiness. Therefore, this study aims to determine whether there is a difference in hardiness among 8th grade students of SMPN 1 Ngunut. The population of this study was 357 with a sample of 192 students (superior class: 63 students and regular class: 129 students) obtained by simple random sampling technique. This study uses the Hardiness Scale (α = 0.919) with 28 items and 4 alternative choices to measure the hardiness level in the students. Based on the results of the independent sample t-test (the sig. (2-tailed) 0.019 < 0.05 and the sig. of variances 0.417 > 0.05), this study found that there are differences in hardiness in 8th grade students of SMPN 1 Ngunut between superior and regular classes. The superior class students have a tendency to have higher hardiness level than the regular class students. Even though overall students in both superior and regular class show hardiness in moderate level, the students from the superior class have the tendency to have hardiness in moderate to high level than the students in regular class that show the tendency to have moderate to low level of hardiness. Keywords: hardiness, junior high school, superior class, regular class